Lactose and its relationship with other milk constituents, somatic cell count, and total bacterial count - Alessio D.R.M.* (2021)
© 2021Lactose has an essential role in milk synthesis, and low lactose content adversely affects dairy product yield. In this study, the association between milk lactose content and other milk constituents (protein and fat), somatic cell count (SCC), and total bacteria count (TBC) was valuated using a database of bulk tank milk (BTM) samples from dairy farms in southern Brazil. Factor and cluster analysis were performed on a dataset containing the fat, protein, and lactose contents, SCC, and TBC of 154,781 BTM samples evaluated by the State Laboratory of Milk Quality (LABLEITE). The factor analysis showed that lactose content in milk was positively associated with fat and protein contents as well as negatively associated with SCC and TBC. The cluster analysis on three clusters showed differences in the fat and protein contents of the BTM samples (P<0.0001) that were not associated with lactose content. In cluster 1, an increase in SCC was associated with a reduction in lactose content. In contrast, in cluster 3, a decrease in lactose content was associated with an increase in SCC and TBC. Increases in SCC or TBC is associated with reduction in milk lactose content without influence from variations in fat and protein contents. Additionally, the evaluation of milk total solids, which represents most milk constituents, is suggested for assessment of milk quality.